Legal Protection of E-Commerce Consumers in Online Transactions in Indonesia - Bramantyo, RizkiYudha; Rahman, Irham (American Journal of Social Sciences and Humanities, 2019)
The use of e-commerce in economic transactions, continues to increase every year. However, various complaints arise from online consumers. They complain of experiencing various cases of fraud through online transactions. Based on this phenomenon, the increase in public consumption of online transactions was not matched by consumer protection that had to be accepted as a customer. The most pressing problem is the weak protection of consumer law. The purpose of this study is to describe the consumer legal protection model in the online transaction process and to ascertain whether the current regulatory framework in Indonesia adequately addresses relevant risks and issues. Based on normative legal studies conducted by researchers that the agreement on e-commerce is inseparable from the basic concept of the agreement established in the UNCITRAL Model Law on eCommerce and the UNCITRAL Model Law on eSignature. Where online trading is basically the same as general trade agreements, only in exchange for transactions conducted with electronic media. We found that to resolve the case of legal protection against consumers is to improve the quality of human resources who must have professional competence, academic competence, resilience, techniques and good attitude and values. Ecommerce contracts must be based on the principles of good trade transactions and enforce the law fairly. We also include that the current laws and regulations on information and electronic transactions for consumer protection have not been able to effectively protect consumers because in practice there are still many cases that cause consumer losses due to violations.